PENDEKATAN ACUAN PENILAIAN DALAM PENDIDIKAN JASMANI - Ngatman, - (Jurnal Pendidikan Jasmani Indonesia, 2015)
Evaluation is one of the important components in every education implementation. Someefforts to improve educaton quality, including physical education, are the improvement oflearning quality and the improvement of its evaluation system. Learning quality has aninterconnected relation with the quality of evaluation system. Good learning system willproduce a good learning quality. This learning quality could be observed from its evaluationresults. Furthermore, good evaluation system will urge teacher to construct a better teachingstrategy and to motivate participants to learn better. Therefore, in an improvement of educationquality, it is needed an upgrading in evaluation system it applied. According to test planningand interpertation of its results, references of evaluation in physical education may be differedinto two, those are : Norm Referred Evaluation (NRE/Penilaian Acuan Norma-PAN) andStandard Referred Evaluation (SRE/Penilaian Acuan Patokan-PAP). Evaluation by usingNRE assumes that the capability and ability of every student is different and could be drawnaccording to normal distribution. Every student's test results are compared with his/her groupscores so that their each position could be observed. Whereas evaluation by using SREassumes that almost every student can learn anything but in a different time/period. Theconsequence of this later evaluation is the presence of remedy program. Interpretation of testresults is always compared with a particular pre-determined criteria. In a further development,evaluation in physical education in order to find out the extent of learning activity resultsuccess of the students can be taken on using evaluation system that uses letter (for tertiaryeducational institution) or using scale between 1 to 10 (for basic education grade up tointermediary education grade"”Base School up to Senior High School). Evaluation by usingscale and letter could be aplied through some ways as follows : (1) distribution gap methods,(2) percentage methods, (3) grade or value compilation methods, (4) normal curve methods,(5) contract-based scoring, and (6) portofolio approach.Keywords : Evaluation Reference Approach, Evaluation System, Physical Education.